Transfer of Energy or Charge between Quasi-Zero-Dimensional Nanostructures. Issue 4 (6th June 2016) - Král, K.; Menšík, M.
ABSTRACT: Transfer rate formula is presented, suitable for analysis of time-resolved experimental data of irreversible transfer of electronic excitation energy, or of electronic charge, between quasi-zero-dimensional (Q0D) nanostructures. This phonon-assisted transfer rate formula is based on quantum kinetic equations theory. The formula deals with the transfer of excitons, or electronic charges, as it depends on temperature, local excitation energies and on the transfer electronic interaction and also on the interaction of the electronic systems with the phonons. The approximation suitable for the so-called incoherent transfer of electronic excitation energy, or of electronic charge, between quantum dots is considered in some detail. The non-adiabatic property of the electrons coupling to the atomic lattice vibrations is said to be responsible for the considered transfer mechanism. The approach is expected to be applicable to the cases of the so-called uphill or downhill transfers. Theoretical analysis is illustrated by numerical computations of exciton transfer between two quantum dots. The expected applicability to exciton and/or charge transfer in polymers is mentioned.